Some New Remarks on the Egyptian Word “ššt“ in Urk IV, 1938, 4 - Bojowald, Stefan (Cultural Arts Research and Development, 2025)
This essay makes a renewed attempt to explain the Egyptian word “ššt“ from Urk IV, 1938, 4. The word appears there next to the “ḏcm“-gold. The investigation thus has a philological focus. The study of philological questions traditionally promises the most benefits in Egyptology. The topic has been rarely addressed in previous research. The expected result therefore has a certain novelty value. The interpretation given here provides for a connection with the root “śḫt“ “to weave“. The “weaving“ of gold can be understood as either “twisting“ jewelry, winding wreaths, or twisting ropes. The use of “ḏcm“-Gold in wreaths can also be proven in other contexts, which also applies to ropes as well. The entire expression “śḫt ḏcm“ “to weave gold“, can be explained as a technical term from the terminology of metal craftsmen. The phenomenon as such can be considered relatively well known. The list of Egyptian examples of metalcraft language is thus further expanded. In this case, one might think of jewelers or toreuters. The two possibilities may be equally valid, but the limited information available does not allow for more detailed statements. The study of socio- or idiodialects is also high on the agenda in neighboring disciplines.